The Outcomes of Organizational Cronyism: A Social Exchange Theory Perspective - Ali, Shahab; Shahzad, Farrukh; Hussain, Iftikhar; Yongjian, Pu; Khan, Muhammad Mahroof; Iqbal, Zafar (Frontiers in Psychology, 2022)
The current research examines the possible outcomes of cronyism like organizational Deviance, Organizational Cynicism and counterproductive work behavior and also investigate the mediating variable violation of psychological contract among cronyism and its possible outcomes. Date is collected from the employees working under different ministries of Azad Jammu and Kashmir, Pakistan like education, forest, sports, information, local government, finance and tourism. The data from 350 employees is gathered through convenience sampling. The data gathering process is conducted in two distinct time spans. Results shows that organizational cronyism significantly and positively relates with Organizational Deviance, Organizational Cynicism and Counter Productive Work Behavior, while Violation of Psychological Contract mediates the relationship among Organizational Cronyism and Organizational Deviance, Organizational Cronyism and Counter Productive Work Behavior. Employees enjoying undue favors from the leadership seems more dedicated towards the organization than the employees which don’t have this favor and ultimate result is negative for the organization.